Media communication analysis of the Instagram account @yasalamfcb in building its Followers’ trust - Syahrul Tanjung; Dani Fadillah; Uspal Jandevi (COMMICAST, 2026)
The development of social media has transformed digital communication into a relational space in which credibility and trust are socially constructed. Although prior studies have extensively examined trust within transactional contexts such as influencer marketing and brand communication scholarly attention to the construction of trust within identity-based communities, particularly football fandom on Instagram, remains limited. This study aims to analyze how the Instagram account @yasalamfcb constructs perceived trust through message structure and symbolic representation. Theoretically, this research integrates Source Credibility Theory and the Social Construction of Reality perspective to elucidate the mechanisms through which trust is formed in digital communities. A qualitative approach was employed, utilizing thematic content analysis of five posts published between March and April 2025, selected purposively, alongside an open-ended survey of five active followers to triangulate audience perceptions. The analysis focused on the dimensions of expertise, trustworthiness, and attractiveness, as well as the processes of externalization, objectivation, and internalization. This study concludes that perceived trust within digital fandom communities emerges from a process of social construction shaped by the interplay between symbolic representation and audience participation. The study’s novelty lies in extending credibility-based trust models to the context of sports communities. However, limitations include the relatively small sample size and restricted observation period. Future research is recommended to employ longitudinal and comparative designs to further advance the analysis of digital trust construction.